PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI TATA USAHA UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARI BANJARMASIN - Nasrullah Nasrullah; Sulastini Sulastini; Muhammad Harlie (Islamic University of Kalimantan MAB Banjarmasin, 2019)
The Role of Climate Organizations and motivations to improve employee performance are very important. This study aims to find out what are the factors that affect the performance of administrative staff at the Islamic University of Kalimantan Muhammad Arsyad Al Banjari Banjarmasin. This study uses quantitative methods, with a total sample of 60 respondents. The data analysis method used is by using multiple linear regression. The results of the study on the effect of work motivation and Organizational Climate on the performance of Administrative staff at the Islamic University of Kalimantan Banjarmasin showed the following results: The first hypothesis states the influence of motivation and Organizational Climate together have a positive influence on the performance of Administrative employees but not significant (meaningless ), The second hypothesis states that the influence of motivation partially has a positive and significant influence on the performance of administrative staff of the Islamic University of Borneo. The third hypothesis states that the influence of Organizational Climate partially has a positive and significant influence on the performance of administrative staff of the Islamic University of Kalimantan Banjarmasin not proven, because the effect is negative and not significant. So it can be concluded that only motivation has a significant effect on the performance of administrative staff of the Islamic University of Kalimantan. Keywords: Motivation, Organizational Climate, Administrative Performance